Mucin-Type O-Glycans: Barrier, Microbiota, and Immune Anchors in Inflammatory Bowel Disease - Zhang Y; Wang L; Ocansey DKW; Wang B; Wang L; Xu Z (Dove Medical Press, 2021)
Yaqin Zhang,1,* Lan Wang,2,* Dickson Kofi Wiredu Ocansey,1,3 Bo Wang,1 Li Wang,4 Zhiwei Xu1 1Key Laboratory of Medical Science and Laboratory Medicine of Jiangsu Province, School of Medicine, Jiangsu University, Zhenjiang, Jiangsu, 212013, People's Republic of China; 2Danyang Blood Station, Zhenjiang, Jiangsu, 212300, People's Republic of China; 3Directorate of University Health Services, University of Cape Coast, PMB, Cape Coast, Ghana; 4Huai'an Maternity and Children Hospital, Huaian, Jiangsu, 223002, People's Republic of China*These authors contributed equally to this workCorrespondence: Li WangHuai'an Maternity and Children Hospital, 104 Renmin Road, Huaian, Jiangsu, 223200, People's Republic of ChinaTel +86 135 1523 0755Email hafybjy@163.comZhiwei XuSchool of Medicine, Jiangsu University, 301 Xuefu Road, Zhenjiang, Jiangsu, 212013, People's Republic of ChinaTel/Fax +86 511 8503 8215Email zhiweixu@ujs.edu.cnAbstract: Inflammatory bowel disease (IBD), which affects about 7 million people globally, is a chronic inflammatory condition of the gastrointestinal tract caused by gut microbiota alterations, immune dysregulation, and genetic and environmental factors. The association of microbial and immune molecules with mucin-type O-glycans has been increasingly noticed by researchers. Mucin is the main component of mucus, which forms a protective barrier between the microbiota and immune cells in the colon. Mucin-type O-glycans alter the diversity of gastrointestinal microorganisms, which in turn increases the level of O-glycosylation of host intestinal proteins via the utilization of glycans. Additionally, alterations in mucin-type O-glycans not only increase the activity and stability of immune cells but are also involved in the maintenance of intestinal mucosal immune tolerance. Although there is accumulating evidence indicating that mucin-type O-glycans play an important role in IBD, there is limited literature that integrates available data to present a complete picture of exactly how O-glycans affect IBD. This review emphasizes the roles of the mucin-type O-glycans in IBD. This seeks to provide a better understanding and encourages future studies on IBD glycosylation and the design of novel glycan-inspired therapies for IBD.Keywords: glycans, inflammation, intestinal mucus, MUC2, microbiota, immunity